A doctrinal research perspective of master's degree students in accounting - Coetsee, D.; Buys, P. (South African Journal of Higher Education, 2018)
This article reflects on the incorporation of doctrinal research in the curriculum of a master’s degree programme in accounting at a South African university. Since accounting concepts, principles and rules are more developed through practice, the question is whether there is place for doctrinal research in accounting research. Doctrinal research is a research approach that focus on the development of the underlying doctrines of a field of enquiry and not on the development of theory per say. In the master’s degree programme doctrinal research is introduced as an alternative research approach to conventional research approaches. The perspective of the master’s degree students is obtained through structured interviews from which different themes are identified by thematic analysis. The participant students agreed that doctrinal research has an important role to play in accounting research. The students also agree that their critical engagement with the underlying doctrines of accounting has improved significantly and that deeper understanding of the concepts and principles of accounting was created.